Comparison between a Single Glucose Challenge Test Procedure and Conventional 2 Hour Oral Glucose Tolerance Test for Diagnosis of Gestational Diabetes Mellitus - Vinod Kumar; Kavita Sharma; Ritu Bhagat; Ahmar Javid (Highlights on Medicine and Medical Science Vol. 7, 2021)
Background: In India, the prevalence of GDM is 8-17 percent, which is quite high. As a result, screening for glucose intolerance is necessary to protect both the mother and the child from negative future consequences. It’s a cause for concern if a considerable portion of the population develops abnormal glucose tolerance. Women with GDM are thus an appropriate population for diabetes prevention. Aim: The study’s goal was to see how well A Single Glucose Challenge Test compared to a traditional 2 hr Oral Glucose Tolerance Test for identifying GDM. Method and Materials: This is a prospective cross-sectional study for a period of one year from November 2010 to October 2011performed at Obstetric & Gynaecology department of Govt. Medical College, Jammu. Results: 334 pregnant women agreed to take part in the study out of a total of 460. The survey was completed by 200 pregnant women out of a total of 334. Subjects at 16-32 weeks of gestation have been evaluated for presence of GDM by doing Single Glucose Challenge Test followed by conventional 2hr Oral Glucose Tolerance Test after 3 days. Conclusion: The current study convincingly demonstrates that 75 gm GCT conducted on pregnant women is a simple, cost-effective, and less time-consuming treatment. As a result, in a nation with low resources yet requiring universal screening, this one-step technique functions as both a screening and a diagnostic method.